Tochastic acceleration of charged particles - Buts, V.A.; Kuzmin, V.V.; Tolstoluzhsky, A.P. (Вопросы атомной науки и техники, 2014)
Comparison of two schemes of stochastic acceleration of charged particles is carried out: at interacting with the field of wave with randomly changed phase and with the field of regular wave in the conditions of overlapping of non-linear resonances. In the absence of conditions of the resonances overlapping the spectral regions of random field which most effectively transfer their energy to particles are found. In all investigated cases, the presence of overlapping non-linear resonances led to more efficient schemes of stochastic acceleration and heating of particles in comparison with schemes involving random fields. Проведено сравнение двух схем ускорения заряженных частиц при взаимодействии с полем волны со случайно изменяющейся фазой и с полем регулярной волны в условиях перекрытия нелинейных циклотронных резонансов. Во всех рассмотренных случаях эффективность ускорения при выполнении условий перекрытия нелинейных циклотронных резонансов оказывается более высокой. Проведено порiвняння двох схем прискорення заряджених частинок при взаємодiї з полем хвилi з фазою, що випадково змiнюється, й з полем регулярної хвилi в умовах перекриття нелiнiйних циклотронних резонансiв. У всiх розглянутих випадках ефективнiсть прискорення при виконаннi умов перекриття нелiнiйних циклотронних резонансiв виявляється бiльш високою.